Strategic investment evaluation - Rishabh Kirpalani; Erik Madsen (Theoretical Economics, 2023)
We study the interaction of incentives to free-ride on information acquisition and strategically delay irreversible investment in environments in which multiple firms evaluate an investment opportunity. In our model, two firms decide how quickly to privately obtain information about the profitability of a project, and when (if ever) to publicly invest in it. Multiple equilibria exist, differing with respect to how much information firms acquire as well as how quickly they invest. The equilibrium which maximizes aggregate payoffs features asymmetric play with distinct leader and follower roles when firms are patient, but features symmetric play when firms are impatient and information acquisition costs are sufficiently high.
Keywords: C73; D82; D83; G24; 330; investment timing; Social learning; strategic information acquisition